Phytochemical Identification of Ethanol Extract of Mahkota Dewa Fruit Flesh (Phaleria macrocarpa [Scheff]) as Antidiabetic - Depi Yuliana; Faizul Bayani; Dwi Monika Ningrum; Neneng Rachmalia Izzatul Mukhlishah (SainsTech Innovation Journal, 2020)
Diabetes mellitus (DM) is one of the biggest disease problems in the world. World Health Organization (WHO) as many as 346 billion people in the world are indicated to have DM. Phaleria macrocarpa [Scheff] Boerl as a native Indonesian medicine is widely used in traditional medicine as an effective medicine against DM, cancer, gout, high cholesterol, and kidney disorders. Phaleria macrocarpa [Scheff] Boerl has saponins and tannins which play a role in reducing blood glucose levels. This study aims to identify the metabolite compounds of Phaleria macrocarpa [Scheff] Boerl extract that have the potential to be anti-diabetic. The research using the TLC method. The results of TLC showed that Phaleria macrocarpa [Scheff] Boerl extract has flavonoids, alkaloids, saponins and tannins.